Statuens indre liv. En tolkning av Juan Muñoz' kunst - Aamold, Svein (Nordlit, 2010)
From the mid-1980's until his untimely death in 2001, the Spanish-born artist Juan Muñoz gained international acclaim for his sculptures, installations and multimedia projects. This article discusses and interprets some of his figurative sculptural works, using concepts such as simulacrum, alienation, allegory, the statue as an autonomous entity, and Walter Benjamin's notion of aura. Muñoz's sculptures strongly invite us into illusionary settings and situations while at the same time leaving us on the outside, as strangers in awkward situations. The theatrical, or performative, character of his larger installations, or tableaux vivants, such as Many Times (1999), questions not only our social and environmental relations, but also our individuality, as if we are confronting mirrors that uncover our vulnerable subjectivity in highly disturbing ways.